2006
DOI: 10.1063/1.2378768
|View full text |Cite
|
Sign up to set email alerts
|

The cumulant two-particle reduced density matrix as a measure of electron correlation and entanglement

Abstract: Several measures of electron correlation are compared based on two criteria: (i) the presence of a unique mapping between the reduced variables in the measure and the many-electron wave function and (ii) the linear scaling of the measure and its variables with system size. We propose the squared Frobenius norm of the cumulant part of the two-particle reduced density matrix (2-RDM) as a measure of electron correlation that satisfies these criteria. An advantage of this cumulant-based norm is its ability to meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
77
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 44 publications
0
77
0
Order By: Relevance
“…It has been reported that correlation measures only depending on the 1-RDM exhibit the same degree of correlation for systems states differing significantly, 22 which is obviously unphysical. However, in quantum systems with twoparticle interactions, there is a one to one mapping between the 2-RDM and the wave function for nondegenerate ground states 48 or for degenerate states which can be distinguished by at least one operator containing just two-particle interactions.…”
Section: A Measure Of the Correlation: Spin Entanglement Contribmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been reported that correlation measures only depending on the 1-RDM exhibit the same degree of correlation for systems states differing significantly, 22 which is obviously unphysical. However, in quantum systems with twoparticle interactions, there is a one to one mapping between the 2-RDM and the wave function for nondegenerate ground states 48 or for degenerate states which can be distinguished by at least one operator containing just two-particle interactions.…”
Section: A Measure Of the Correlation: Spin Entanglement Contribmentioning
confidence: 99%
“…33 Hence, Ref. 22 concluded from this mapping that the 2-RDM is needed for a correlation measure of atomic and molecular systems in order to avoid the above mentioned drawback. For these reasons and according to our previous studies involving the quantities defined by Eqs.…”
Section: A Measure Of the Correlation: Spin Entanglement Contribmentioning
confidence: 99%
See 3 more Smart Citations